Adaptability in Interior Space: Public Housing for Lower-Middle Income Group in Dhaka - Yasmin, Dilruba; Nilufar, Farida (UI Scholars Hub, 2023)
This research examines the spatial characteristics of domestic spaces, their use, and adaptations to analyse their changing morphology. It also examines inhabitants' preferences and requirements for the functional utilisation of the interiority of dwellings. Fifteen apartments in Dhaka were analysed to compare the initial design with the later modifications by occupants. The research followed an ethnographical method to depict the lives and experiences of individuals. The research has identified significant changes in activity zoning and their pattern, thus creating a new spatial organisation of the house that is different from the original design. Activity analysis reveals that most spaces are multipurpose; moreover, maintaining segregation and privacy is challenging. Lack of privacy is a significant concern during the alterations. Households are usually the extended type with a large number of members. Hence, this research finds the need for extra rooms within the given space. Another reason for alterations is the need for adequate functional space. A discrepancy exists between the dwelling space design and the actual needs and preferences of the occupants. This discrepancy highlights gaps between the designer's solution and the user demand, which prompts adjustments in the aspirations of the house through modifications and adaptations.